Influence of dietary inclusion of tannin extracts from mimosa, chestnut and tara on volatile compounds and flavour in lamb meat. (February 2021) - Del Bianco, Silvia; Natalello, Antonio; Luciano, Giuseppe; Valenti, Bernardo; Campidonico, Luca; Gkarane, Vasiliki; Monahan, Frank; Biondi, Luisa; Favotto, Saida; Sepulcri, Angela; Piasentier, Edi
Abstract: Tannins are compounds able to form complexes with proteins limiting their ruminal degradation and thus the synthesis of some odour-active compounds may be inhibited . Tannins are broadly divided in condensed tannins (CT) and hydrolysable tannins (HT). The study aimed to assess the influence of dietary inclusion of three commercial tannin extracts, namely mimosa ( Acacia mearnsii ; CT), chestnut ( Castanea sativa ; HT) or tara ( Caesalpinia spinosa ; HT) on volatile profile and flavour of meat and kidney fat from lambs. Comisana male lambs were divided into four groups ( n  = 9 each) and fed for 75 days with a concentrate-based diet (CON) or CON supplemented with 4% of one of the tannin extracts. Tannins reduced "pastoral" odour in perirenal fat of lambs the meat of which was characterized by a very low perception of this attribute. It may be assumed that p -cresol and 8-methylnonanoic acid mostly contributed to "pastoral" odour expression in the diet without condensed or hydrolysable tannins.